A Blockchain-Based Optimization Model for Smart 4PL Network Design in Off-Site Construction - Karimi, Behnam; Mohammadpour Omran, Mohammad (Supply Chain and Operations Decision Making, 2026)
This study proposes a Blockchain (BC)-integrated Fourth-Party Logistics (4PL) model to improve efficiency and Transparency (TR) in Off-Site Construction (OSC) supply chains. A bi-objective optimization model is developed to minimize total network costs and maximize transparency, determining optimal locations for pre-processing centers, selection of Third-Party Logistics (3PL) providers, assignment of installation teams, and material flow planning. Validation through General Algebraic Modeling System (GAMS) software and sensitivity analysis shows the model significantly reduces logistics costs and delays. Notably, partial BC integration achieves 65% transparency with only a 3.75% cost increase, offering a cost-effective solution. The framework enables construction stakeholders to leverage Industry 4.0 technologies for enhanced collaboration and risk mitigation.